HUBUNGAN KEPATUHAN PERAWAT DALAM PENERAPAN STANDAR OPERASIONAL PROSEDUR (SOP) TEKNIK MENYUNTIK DENGAN PENCEGAHAN KEJADIAN TERTUSUK JARUM DI RUMAH SAKIT - Ahsan Ahsan; Niko Dima; Kadek Chintya Nurlita Widyahastuti (Jurnal Kesehatan Mesencephalon, 2019)
Nurses in hospitals are at risk of disease and occupational accidents in accordance with the actions taken. The most common occupational accident is used needle stick puncture wound while taking an injection, more commonly known as the Needle Stick Injury (NSI). If nurses do not comply with the application of SOP of injecting techniques, this can cause needle-punctured occupational accidents that have an impact on the transmission of pathogenic infections that endanger the nurses and patients them selves. Therefore, the role of SOP program is very important to avoid occupational accidents, specifically the incidence of Needle Stick Injury. The aim of this study is to identify the relationship between nurse compliance on the application of injecting technique standard operating procedure with the prevention of needle stick injury in the hospital. The method of this study is Descriptive correlational study with cross sectional design approach by using observations to adhere to the application of injecting and prevention of needle stick injury incidence. The results of the study fromI48 nurses in threeIclass III in patient wards at Kanjuruhan Hospital showed that almost all implementing nurses adhered to the implementation of Injecting technique SOP were as many as 46 nurses (95,8%) and a small number of implementing nurses were less compliant as many as nurses (4,2%). Observation results of NSI incidence prevention of nurses found that almost all nurses had safe actions in the prevention of NSI incidence as many as 38 nurses (79,2%) and a small number of nurses had unsafe actions Ias much as 10 nurses (20,8%). Spearman rank test obtained by the correlation coefficient of (0,406) with a significance value of (0.004) lesser α (0,05). It can be concluded that there is a significant relationship between nurse adherence in the application of Injecting technique SOP with the prevention of needle stick injury incidence in hospital. Keywords: Compliance of injecting techniques, needleIstick injury prevention